2018
DOI: 10.3389/fimmu.2018.00859
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Exploits Wnt Signaling Pathway to Promote Its Intracellular Replication in Macrophages

Abstract: During the acute phase of Trypanosoma cruzi infection, macrophages can act as host cells for the parasites as well as effector cells in the early anti-parasitic immune response. Thus, the targeting of specific signaling pathways could modulate macrophages response to restrict parasite replication and instruct an appropriate adaptive response. Recently, it has become evident that Wnt signaling has immunomodulatory functions during inflammation and infection. Here, we tested the hypothesis that during T. cruzi i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 63 publications
7
57
0
Order By: Relevance
“…To evaluate the effect of Wnt signalling inhibition on parasitaemia and heart parasitism in an animal model of chronic Chagas'disease, BALB/c mice were infected with a non-lethal doses of Tulahuen strain of T. cruzi and treated with IWP-L6 (IWP-L6 mice) or vehicle (Control mice) at days 5;8;11 and 14 p.i. Similar to that observed in B6 mice (29), IWP-L6 mice showed lower parasitaemia and heart parasite load than Control mice in the acute phase of the infection. ( Figure 1A and B).…”
Section: Inhibition Of Wnt Signalling Controls Parasite Load In Infecsupporting
confidence: 80%
See 1 more Smart Citation
“…To evaluate the effect of Wnt signalling inhibition on parasitaemia and heart parasitism in an animal model of chronic Chagas'disease, BALB/c mice were infected with a non-lethal doses of Tulahuen strain of T. cruzi and treated with IWP-L6 (IWP-L6 mice) or vehicle (Control mice) at days 5;8;11 and 14 p.i. Similar to that observed in B6 mice (29), IWP-L6 mice showed lower parasitaemia and heart parasite load than Control mice in the acute phase of the infection. ( Figure 1A and B).…”
Section: Inhibition Of Wnt Signalling Controls Parasite Load In Infecsupporting
confidence: 80%
“…On the other hand, it is important to take into account that not only immune system cells and their products but also many other signalling systems and complex cellular interactions between recruited and cardiac cells (myocytes, fibroblasts, endothelial cells, smooth muscle cells, epicardial cells) can participate in the damage and repair processes that occur after the parasite-or inflammation-induced injury. Thus, during T. cruzi infection, the Wnt signalling system would not only be involved in modulating Mo phenotype and function, as we have previously demonstrated (29), but could also play a role in orchestrating the cardiac damage that follows a parasite infection as it has been shown in ischemia or hypertrophy (reviewed by Deb, A (43)). Here, we show evidences that inhibition of Wnt was able to (29), we speculate that this treatment contributes to shift the characteristic Th2-type immune response developed by BALB/c mice to a Th1-type.…”
Section: Discussionmentioning
confidence: 76%
“…Next, we carried out the following experiments in vivo and found that in DKK1 low -ERC (ERC pretreated with IL-1β) group, clinical characters and pathological manifestations of colitis were strikingly ameliorated, in which the immune-regulatory effects of ERCs may be enhanced by low DKK1 production, as a result of Wnt/β-catenin pathway being activated [34,47]. Comparing with that in DKK1 high -ERC (ERC pretreated with GC) group, we con rmed that DKK1 plays a vital role in affecting therapeutic function of ERCs on experimental colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying such process needs to be further investigated but our results suggest that transactivation of β-catenin in epithelial cells and in macrophages could play an important role. Accordingly, β-catenin enhances intestinal epithelial cell proliferation [40] and in the absence of E-cadherin, a well-known β-catenin inhibitor, necrosis and anoikis sparked in IECs during colitis [41] , [42] . Such process could be directly related to the hyperproliferation induced by β-catenin.…”
Section: Discussionmentioning
confidence: 99%